Greenland, fjord landscape at Goodenough Land, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig 2 - The head of Franz Josef Fiord and Nathorst Peak, 8480 feet. July 31, 1931. (Caption from Boyd, L. A., & Menzies, R. H. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Fiords. Geographical Review, 22(4), 530.) Goodenough Land, Nathorst Peak, Nordenskiold Glacier, Greenland Boyd, L. A. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Flords. Geographical Review, 22(4), 529-561.